Analisis indikator komunikasi dalam keberhasilan proyek konstruksi: studi literatur - Alvia Nayla Wibowo (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Construction projects are complex activities involving multiple stakeholders and constrained by time, cost, and quality. In practice, communication has been identified as a critical non-technical factor influencing project success. This study aims to analyze the role of communication in construction project success and to identify the most dominant communication indicators based on previous studies. The research employed a literature review approach by analyzing 20 national scientific journals supported by relevant book on project management and organizational communication. Data were analyzed using content analysis to identify the most frequently discussed and statically dominant communication indicators. The result shows that most studies indicate a significant relationship between communication and project performance, particularly in terms of time, cost, quality, and risk control. Among the identified indicators, information delivery emerges as the most consistent and statistically dominant factor. Other indicators such as message clarity, two-way communication, communication technology usage, coordination relationships, and performance reporting also contribute to project effectiveness, although not always as primary variables. This study concludes that construction project success is not solely determined by technical aspects but is strongly influenced by the effectiveness of the communication system implemented in project management.